Using Corpus-Based Reading Materials to improve EFL Students Academic Writing Accuracy - Aliya Noor Cahyani; Atalisi Zalukhu; Mariska Intan Sari (Universitas Islam Negeri Palopo, 2026)
This study investigates the effect of using corpus-based reading materials on EFL students’ academic writing accuracy. Employing a quantitative approach with a quasi-experimental design, the study involved 50 undergraduate students from Institut Bisnis dan Komputer Indonesia, divided into an experimental group and a control group. The experimental group received instruction through corpus-based reading materials, while the control group was taught using conventional reading texts. Data were collected through pre-test and post-test writing tasks and analyzed using descriptive statistics and t-test analysis. The findings revealed that the experimental group demonstrated significantly greater improvement in writing accuracy compared to the control group. The results showed substantial gains in grammatical accuracy, vocabulary use, and sentence structure, indicating that corpus-based reading materials effectively enhance students’ ability to produce accurate academic writing. In addition, the analysis of performance levels revealed a significant shift from lower to higher proficiency categories among students in the experimental group. These findings highlight the importance of integrating corpus-based approaches into reading and writing instruction. This study suggests that corpus-based reading materials serve as an effective pedagogical tool to improve EFL students’ academic writing accuracy.